Hybrid teaching in deaf education during the pandemic: learning challenges - Pinheiro, Andrea; Sena, Lílian de Sousa; Serra, Ilka Márcia Ribeiro de Souza (Educação On-line, 2023)
Abstract 2020 was an especially important year to (RE) think about education in Brazil. It was an year in which the educational community needed to re-signify itself, considering the new challenges imposed by the Covid-19 pandemic. In this sense, this work aims to show what has occurred in the academic environment after the pandemic onset. This work investigated under the bias of a qualitative analysis through questionnaires the main difficulties encountered by teachers of inclusive high school classrooms and professionals of multifunctional resource rooms in the learning process of deaf students, with the use of technologies. The results indicate efforts in deaf students' education once the changes of educational paradigms re-signified agents, mode/means, instruments, and educational purposes. Moreover, it points the need for innovating educational practices. Resumo O ano de 2020 foi muito importante para (re)pensar a educação no Brasil, por ser aquele em que a comunidade educacional precisou se ressignificar perante os novos desafios impostos pela pandemia de Covid-19. Nesse sentido, o objetivo do trabalho é fazer um recorte para o que tem acontecido no meio acadêmico após ser decretada a pandemia. Este trabalho investiga, sob o viés da análise qualitativa, utilizando questionários, as principais dificuldades encontradas por docentes de salas inclusivas do ensino médio e profissionais de salas de recursos multifuncionais, no processo da aprendizagem de alunos surdos, com o uso das tecnologias. Os resultados apontam esforços no contexto do ensino de alunos surdos, visto que as mudanças de paradigmas educacionais ressignificaram agentes, modo/meio, instrumentos e finalidades educacionais, além de apontarem a necessidade de inovação das práticas educativas.